Effect of Phage SAvB14 combined with antibiotics on Staphylococcus aureus variant bovis - Y. V. Horiuk; M. D. Kukhtyn; V. V. Horiuk; V. A. Sytnik; O. O. Dashkovskyy (Regulatory Mechanisms in Biosystems, 2021)
Because using antimicrobial drugs leads to development of resistance among bacterial isolates, the treatment with antimicrobial drugs in human and veterinary medicine in general should be reduced. Currently, therapeutic use of bacteriophages may be an alternative or addition to the treatment of bacterial infections of animals. The article presents the results of studying the effect of bacteriophage Phage SAvB14 on microbial biofilms of Staphylococcus aureus variant bovis both alone and in complex with antibiotics. For this purpose, we used strain S. aureus var. bovis 1491 f and bacteriophage Phage SAvB14, isolated at dairy farms. The effect of combined application of phage and antibiotics (gentamicin, tetracycline, сeftriaxone and enrofloxacin) were assessed after simultaneous and subsequent introduction of Phage SAvB14 in the dose of 105 plaque-forming units per milliliter (PFU/mL) and corresponding concentrations of antibiotics to 24h biofilms. We determined that of the tested antibiotics, only gentamicin and ceftriazone exerted synergic effects in combinations with Phage SAvB14. Combination treatment using gentamicin and the phage decreased the amount of S. aureus in biofilm by 39.81 times compared with the phage-only treatment. Significant synergic effect was also taken by ceftriaxone – it killed 1.26 times more bacteria in combination with the phage than alone. Other antibiotics did not increase antibiotic activity of the phage. Specifically, 1.11 and 1.26 times more vital cells remained after the actions of tetracycline and enrofloxacin than after the exposure to the bacteriophage only. Therefore, the obtained results indicate that biofilm of S. aureus var. bovis may be eliminated using Phage SAvB14 as an individual antibacterial agent, as well as in complex with antibiotics. However, complex treatment would imply introducing the phage and then antibiotic some time later.